A scoping review of persistent symptoms after COVID infection at different follow-up periods - P R Sreelakshmi; Babasaheb Vishwanath Tandale; Abhijeet V Jadhav; Rupali R Vaidya; Atul M Walimbhe; Santoshkumar Jadhav (Wolters Kluwer Medknow Publications, 2023)
The clinical entity termed as long COVID has gained importance in the recent past. As this phenomenon is still evolving, it is important to document the magnitude of the syndrome during different time periods. This scoping review attempts to synthesize evidence generated from longitudinal studies which have follow-up periods beyond 3 months, up to 12 months. The review also documents the reported prevalence of long COVID for the different regions of the World Health Organization. Longitudinal studies published till March 2022 were systematically searched on PubMed, Google Scholar, and medRxiv. Among the identified 594 studies, 48 were included in this review. Data from selected studies were synthesized. The overall pooled prevalence of long COVID was 49% (40%-58%). The pooled estimates after 3 months, 4-6 months, 7-9 months, and 10-12 months were 44% (32%-57%), 50% (43%-57%), 49% (37%-62%), and 54% (46%-62%), respectively. Eastern Mediterranean Region (EMR) had the highest pooled prevalence of 63% (34%-92%] and the South East Asian Region (SEAR) had the least pooled estimate of 15% (10%-21%). The study brings out the high prevalence of long COVID even after 12 months of follow-up. It also shows the regional differences in the reported prevalence of the syndrome. This review highlights the need for well-planned follow-up studies, especially in developing nations to understand the magnitude and the pattern of long COVID-related symptoms as they emerge.